The refugees’ mobilization and its languages. Ethnographic notes on a field of interlocution in transformation - Zelaya, Silvia (Cadernos de Campo (São Paulo, 1991), 2017)
The objective of this article is to discuss, based on ethnographic experiences in events of visibilization and sensitization of the migratory is- sue in the city of São Paulo, how the forms of political mobilization produced by the Group of Refugees and Homeless Immigrants (Grupo de Refugiados e Imigrantes Sem Teto – Grist), can be seen as privileged scenarios for thinking about the current migratory context as a field of interlocution in transforma- tion. I understand that in addition to the self-representation proposal, these demonstrations – from talks on the war in the Democratic Republic of Congo to musical performances in bars and restaurants, besides lectures in libraries and educational institutions – can stimulate the construction of more plural less stereotyped representations of the immigrants as well as attitudes of critical confrontation to other migrant groups and communities.